2020
DOI: 10.1101/2020.02.28.970616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amygdala-cortical control of striatal plasticity drives the acquisition of goal-directed action

Abstract: The acquisition of goal-directed action requires the encoding of specific action-outcome associations involving plasticity in the posterior dorsomedial striatum (pDMS). We first investigated the relative involvement of the major inputs to the pDMS argued to be involved in this learning-related plasticity, from prelimbic prefrontal cortex (PL) and from the basolateral amygdala (BLA). Using ex vivo optogenetic stimulation of PL or BLA terminals in pDMS, we found that goal-directed learning potentiated the PL inp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Thus lOFC→BLA→lOFC is a functional circuit for the encoding (lOFC→BLA) and subsequent use (BLA→lOFC) of sensory-specific reward memories. Although the BLA-lOFC circuit is not the only amygdala circuit involved in sensory-specific reward memory (Corbit et al, 2013; Fisher et al, 2020; Kochli et al, 2020; Morse et al, 2020; Parkes & Balleine, 2013), we have found it to be a critical one, consistent with prior evidence from disconnection lesions in non-human primates (Baxter et al, 2000; Fiuzat et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus lOFC→BLA→lOFC is a functional circuit for the encoding (lOFC→BLA) and subsequent use (BLA→lOFC) of sensory-specific reward memories. Although the BLA-lOFC circuit is not the only amygdala circuit involved in sensory-specific reward memory (Corbit et al, 2013; Fisher et al, 2020; Kochli et al, 2020; Morse et al, 2020; Parkes & Balleine, 2013), we have found it to be a critical one, consistent with prior evidence from disconnection lesions in non-human primates (Baxter et al, 2000; Fiuzat et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The encoding of such information would have been disrupted by bilateral lOFC→BLA or BLA inactivation during learning, but in the disconnection experiment could have been learned in the hemisphere that did not receive lOFC→BLA inactivation and subsequently retrieved via an alternate BLA pathway. Indeed, BLA→lOFC are not the only amygdala projections involved in reward memory (Beyeler et al, 2016; Corbit et al, 2013; Fisher et al, 2020; Kochli et al, 2020; Morse et al, 2020; Parkes & Balleine, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2). We next assessed whether the chemogenetic manipulation during training prompted goal-directed control by exposing both D2-hM3Dq-eGFP and Sham aged groups to single outcome devaluation procedures (Fisher et al, 2020): on days 15 and 17, mice were sated on either the instrumentally-conditioned outcome (devalued O) or regular chow (valued O) for 1h followed by an extinction test, in which the trained lever was present but no outcome was delivered (Fig. 5e).…”
Section: Resultsmentioning
confidence: 99%
“…The cellular plasticity in the pDMS necessary for goal-directed action is thought to reflect the integration of glutamatergic inputs from cortical, thalamic and limbic regions with the input from midbrain dopaminergic neurons (Bradfield et al, 2013; Fisher et al, 2020; Holly et al, 2019; Lee et al, 2020; Nonomura et al, 2018; Peters et al, 2021; Reynolds et al, 2001; Shiflett and Balleine, 2011). Nevertheless, although much has been learned about the role of striatal dopamine in the cellular and circuit level plasticity necessary for reflexive motor movements and skills (Klaus et al, 2017; Park et al, 2020; Santos et al, 2015) relatively little is known about the specific role that dopamine activity plays in the acquisition and performance of goal-directed actions.…”
Section: Dopamine Release In the Pdms Becomes Lateralized As Goal-dir...mentioning
confidence: 99%
“…Recent evidence suggests that action-outcome encoding depends on a prefronto-striatal circuit focused on the posterior dorsomedial striatum (pDMS)(Balleine, 2019; Balleine & O’Doherty, 2010; Hart, Bradfield, & Balleine, 2018; Hart, Bradfield, Fok, et al, 2018) with initial learning and the subsequent updating of these associations involving changes in plasticity at two types of principal neuron(Balleine et al, 2021): the striato-nigral direct spiny projection neurons (dSPNs), which express dopamine D1 receptors, and striato-pallidal indirect SPNs (iSPNs) expressing the D2 receptor(Gerfen & Surmeier, 2011) (Matamales et al, 2020; Peak et al, 2020). Importantly, this plasticity appears to reflect the integration of glutamatergic inputs from cortical, thalamic and limbic regions with the input from midbrain dopaminergic neurons(Bradfield et al, 2013; Fisher et al, 2020; Holly et al, 2019; J. Lee et al, 2020; Nonomura et al, 2018; Peters et al, 2021; Reynolds et al, 2001; Shiflett & Balleine, 2011).…”
mentioning
confidence: 99%